Предмет: Алгебра,
автор: Айдана87
Помогите пожалуйста решить уравнение:
(х+1)^3-(х-1)^3=х(6х+2)
Ответы
Автор ответа:
0
a³-b³=(a-b)(a²+ab+b²)
---------------------------------------
(x+1-x+1)(x²+2x+1+x²-1+x²-2x+1)=6x²+2x
2*(3x²+1)=6x²+2x
6x²+2=6²x+2x
2x=2
x=1
---------------------------------------
(x+1-x+1)(x²+2x+1+x²-1+x²-2x+1)=6x²+2x
2*(3x²+1)=6x²+2x
6x²+2=6²x+2x
2x=2
x=1
Похожие вопросы
Предмет: География,
автор: Pollydaeny
Предмет: Қазақ тiлi,
автор: nygmetova
Предмет: Математика,
автор: Damir87001553101
Предмет: Обществознание,
автор: bvbndghdmhmhj
Предмет: Математика,
автор: Аноним